Adventure - London, Jack, 1876-1916 (Floating Press, 2010)
Though novelist Jack London is best known for the paean to natural wonder that is The Call of the Wild, he had an activist side, as well. In Adventure, London describes and skewers the plantation system of The Solomon Islands in a devastating take-down that is equal parts adventure tale and social justice tract.